Deus escreve certo por linhas tortas. A estética caipira de Santo Antônio e a vaca - Célia Tolentino (Caravelle)
If cinema is an essentially urban means of expression, the fruit of technique and industry, can a film narrator express in a film’s esthetics a caipira’s « Weltanschauung » (world vision or philosophy) ? We suggest, agreeing with Benjamin – who considers that narrative is the best expression of manual and traditional work’s time– that the story related by the film A proteção de Santo António constitutes a cinematographic narrative which can be classified as caipira. Tenderly called by the audiences Santo António e a vaca, this film was supported by a large part of the population for its making, which allowed to fill in the lack of technical and financial resources. Here, we defend the idea that the visible traces of this work in this particular film, turns it into a real filmic narrative and also into a sincere tribute to caipira culture.